Neutralizing antibody titers to Omicron six months after vaccination with BNT162b2 in Colombia - Zapata-Cardona, María I.; Flórez-Álvarez, Lizdany; Lopera, Tulio J.; Chvatal-Medina, Mateo; Zapata-Builes, Wildeman; Diaz, Francisco J.; Aguilar-Jimenez, Wbeimar; Taborda, Natalia; Hernandez, Juan C.; Rugeles, Maria T. (Frontiers in Immunology, 2022)
The emergence of the Omicron variant has generated concerns about the efficacy of COVID-19 vaccines. We evaluated the serum neutralizing activity of antibodies against the Omicron (lineage BA.1.1) by plaque reduction neutralizing test, as well as its correlation with age and gender, in a Colombian cohort six months after being vaccinated with BNT162b2 (Pfizer/BioNTech). Compared to all other variants analyzed, a significantly lower neutralizing activity (p<0.001) was observed against Omicron. Interestingly, older individuals exhibited lower titers against Omicron than those younger than 40. No statistical differences in neutralizing activity were observed according to gender. Our results showed that two doses of BNT162b2 might not provide robust protection against the Omicron variant over time. It is necessary to consider including changes in the composition of the vaccines to protect against new emerging variants of SARS-CoV-2 and campaigns to implement additional booster vaccinations.